P041 Disintegrating sexual and reproductive healthcare? our patients' views. (8th June 2017) - Bull, Lauren; Rayment, Michael; Jones, Rachael; Cohen, CE
Abstract : Introduction: The drive for integrated sexual and reproductive health services has improved access for women. However, councils in our area indicate Level 3 services will only provide initial contraceptive scripts, redirecting women to primary care services thereafter. We canvassed service users' opinions. Method: Women dispensed with pill/patch/ring/injection prescriptions during February 2017 were invited to complete an anonymous online survey. Results: The response rate was 46% (92 responses over four weeks). Half lived locally. A majority were aged 18–34 years (77, 84%), of white ethnicity (73, 80%) and in full-time employment (78; 84%). Most were GP registered (77, 84%). Most were pill users (62, 67%). Over half sought a repeat prescription (52, 57%), 24 (26%) were new starters and 18 (20%) requested a sexual health screen. Two thirds (63, 69%) walked-in without an appointment. One third (32, 35%) stated they couldn't be seen at their GP. Ease of access was the main driver for attendance (76, 77%). Other key reasons for choosing our service: access to their method of choice (50, 54%); professional advice about methods (34, 37%); to ask sexual health advice (18, 20%); to receive STI screening (21, 23%). 78 women (87%) cited they had concerns about the council's proposal, with 69 (85%) stating access to primary care concerned them. Discussion: This survey highlights the value to patients of easy access to skilled professionals who provide comprehensive sexual and reproductive healthcare. Significant concerns were raised about this proposal, which ignores both the need and value women place on integrated services like ours.